2021
DOI: 10.34172/joddd.2021.048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of laser-microtexturing on bone and soft tissue attachments to dental implants: A systematic review and meta-analysis

Abstract: Background. It is critical to understand laser-microtextured implant collars’ influence on peri-implant pocket depths and marginal bone levels, especially in crucial areas. The present review investigated the peri-implant marginal bone loss (MBL) and pocket depths and failure rates of dental implants with laser-microtextured collars. Methods. An electronic search was run in the PubMed and Embase databases until September 15, 2019. Randomized and prospective clinical studies comparing peri-implant MBL and pocke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…A recent review reported that the fibro-collagenous attachment around the microgrooved neck might stabilize the bone and reduce crestal bone resorption [ 28 ]. Previous in vitro investigations revealed osteoblast attachment on the laser-microtextured neck and cell alignment along the microgroove directions [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent review reported that the fibro-collagenous attachment around the microgrooved neck might stabilize the bone and reduce crestal bone resorption [ 28 ]. Previous in vitro investigations revealed osteoblast attachment on the laser-microtextured neck and cell alignment along the microgroove directions [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is because the maxilla and mandible differ in bone quality ( Dank et al, 2019 ). Besides microgrooves, other factors influencing MBL include bone-grafting, placement of implant in fresh alveolar sockets, duration of healing, existing occlusion, angulation of implant, and loading strategy ( Koodaryan and Hafezeqoran, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The micron-level surface topography promotes more effective interlocking of the bone at the implant interface ( Barfeie et al, 2015 ). In a laser micro-textured surface (LMS) design, a laser ablation technique powered by a computer is applied to the implant neck to achieve 8–12 µm microgrooves ( Chen et al, 2017 , Koodaryan and Hafezeqoran, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tooth #9 was extracted under oral conscious sedation with least traumatic technique [15] utilizing Periotomes (BioHorizons, Birmingham, AL, USA), and a 4.6X12mm, 3.5 mm platform implant was inserted (Tapered Internal Plus LaserLok, BioHorizons, Birmingham, AL, USA). This specific implant was chosen to enable "platform switching" [8] along with its LaserLok characterization at the cervical area [10].…”
Section: Case Presentationmentioning
confidence: 99%